2019
DOI: 10.14740/jocmr3669
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Complications in Warfarin-Treated Patients Admitted to the Emergency Department

Abstract: BackgroundIncreased use of warfarin for the treatment and prophylaxis of many diseases has increased the frequency of adverse events. Emergency departments (EDs) are the first places where early interventions for bleeding and other complaints related to warfarin use are performed. This study assessed the characteristics of patients receiving warfarin and the risk factors for bleeding complication among those admitted to the ED.MethodsPatients admitted to the ED for any reason other than trauma during a 1-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…One strategy to allow for HSA to release warfarin has been using other drugs that also have a high affinity for HSA. These release-aided drugs are usually over-the-counter drugs that people can use along with their major medicines. Nevertheless, sometimes displacement of warfarin bound to HSA results in an increase in warfarin free concentration, which could then elevate the risk of bleeding . Consequently, the consumption of other drugs with warfarin should be considered as a crucial point, and the concentration of warfarin in the blood must be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…One strategy to allow for HSA to release warfarin has been using other drugs that also have a high affinity for HSA. These release-aided drugs are usually over-the-counter drugs that people can use along with their major medicines. Nevertheless, sometimes displacement of warfarin bound to HSA results in an increase in warfarin free concentration, which could then elevate the risk of bleeding . Consequently, the consumption of other drugs with warfarin should be considered as a crucial point, and the concentration of warfarin in the blood must be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…The study found the incidence of bleeding in four patients with an average age of 70.25±5.32 years. Hematuria becomes a clinical manifestation of major bleeding in warfarin users, which is also found in a retrospective cross-sectional study involving 96 patients (58.82%) (Ozturk et al, 2019). In addition to the elderly age, heart disease and hypertension are associated with an increased risk of bleeding in treatment with warfarin which is also found in these four patients (Shoeb & Fang, 2013).…”
Section: Resultsmentioning
confidence: 56%
“…Monteiro et al found that the annual incidence of minor bleeding was 17.7% 24 . Oztürk et al reported that 33.3% of the patients had experienced minor and/or major bleeding at least once during 1year period, moreover bleeding complications detected in 38.9% of patients ≥ 65 years of age and in 26.2% of patients <65 years of age 25 . A recent study showed that the clinically relevant minor bleeds and severe bleeding events were found 66.7% in the warfarin treatment group during the two-year follow-up 26 .…”
Section: Discussionmentioning
confidence: 99%